Efficacy and safety of paritaprevir/ritonavir, ombitasvir, and dasabuvir with ribavirin for the treatment of HCV genotype 1b compensated cirrhosis in patients aged 70 years or older. Issue 50 (December 2017) - Trifan, Anca; Stanciu, Carol; Gheorghe, Liana; Iacob, Speranta; Curescu, Manuela; Cijevschi Prelipcean, Cristina; Stefanescu, Gabriela; Girleanu, Irina; Chiriac, Stefan; Mihai, Catalina; Brisc, Ciprian; Goldis, Adrian; et al.
Abstract : Abstract: Advanced age has been a major limitation of interferon-based treatment for chronic hepatitis C virus (HCV) infection because of its poor response and tolerability. Direct-acting antiviral (DAA) drug regimens are safe and highly effective, allowing administration of treatment also in elderly. This study aims to assess the efficacy and safety of paritaprevir/ritonavir, ombitasvir, and dasabuvir (PrOD) with ribavirin for the treatment of patients aged ≥70 years with HCV genotype 1b compensated cirrhosis. A total of 1008 patients with HCV genotype 1b compensated cirrhosis were prospectively treated with PrOD + ribavirin for 12 weeks, between December 2015 and July 2016. Sustained virologic response 12 weeks after the end of treatment (SVR12), adverse effects (AEs), comorbidities, discontinuation, and death rates were recorded. Efficacy and safety of therapy were assessed in patients aged ≥70 years and compared with data from patients <70 years. There were 117 patients aged ≥70 years, preponderantly females (58.9%), mean age 73.3 ± 2.8 years (range 70–82), and 37 (31.6%) were treatment-experienced. Comorbidities were reported in 60.6% of patients ≥70 years and in 39.8% of those <70 years ( P  < .001). SVR12 rates based on intention-to-treat and per-protocol analyses were 97.4% and 100%, respectively, in patients ≥70 years, compared to 97.8% and 99.6%, respectively, in patients <70 years ( P  = ns and P  = ns). Severe AEs were reported in 4 (3.4%) patients ≥70 years, compared to 23 (2.6%) in those <70 years ( P  = ns). One death was recorded in a patient aged 79 years (0.9%) and 6 deaths (0.8%) in those <70 years ( P  = ns). Treatment with PrOD + ribavirin in patients 70 years of age or older with HCV genotype 1b compensated cirrhosis proved as effective, safe, and well tolerated, as it did in younger patients.